Playing with the Dramaturgical Tradition in Anna Kashina’s Play „Duma” - Sikora-Krizhevska, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article deals with the combination of classical and innovative artistic techniques in the play Duma by Anna Kashina. Playing with the dramaturgical tradition on different levels is described and it is shown to embrace the system of characters, the content of the stage directions (the insertion of video projections, moving the action to auditorium) and also the composition of the play. Kashina’s play is discussed by the author as a work whose poetics is determined by the aesthetics of modern visual media as well as by the literary tradition.